Kuliner Tradisional Nusantara Sebagai Bentuk Adaptasi Budaya pada Channel Youtube Shanty di China - Roy Antok Wibowo; Mochammad Ichdah Asyarin Hayau Lailin; Ratnaningrum Zusyana Dewi (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Traditional Nusantara culinary is a food that is a characteristic or identity of Indonesia and regions that are inherited from generation to generation, this archipelago culinary has a close relationship and is related to the people of Indonesia. Culinary has an important role for the adaptation process, if there is an Indonesian citizen who is in a domestic relationship with a foreign citizen. This research aims to find out how traditional culinary in the archipelago can support the cultural adaptation process. This research uses Eriyanto's qualitative content analysis method and uses the theory of cultural adaptation and this research was conducted by observing Shanty's YouTube channel in China who is an Indonesia citizen who has married a foreign citizen and chose to live in China. Then document by screen capturing the content of Shanty's YouTube channel in China which depicts cultural adaptation through culinary and conducting a literature study by searching for various related journals. The author has conducted research on culinary adaptations on Shanty's YouTube channel in China. The findings of this study can be concluded that on Shanty's Youtube channel in China, most of the ways of adapting using traditional Nusantara cuisine such as selling traditional Nusantara food through food trucks so that here it is illustrated that the many varieties of Nusantara culinary that are sold have an important role in supporting the cultural adaptation process. The implications that occur here can certainly attract the surrounding community to try and taste the culinary, if the person feels like or is interested in trying it and then the next day he comes back to buy the food again, then it can be ensured that cultural adaptation through culinary will be successful because unconsciously there has been a closeness between Shanty in China and the Chinese people.